2019
DOI: 10.35542/osf.io/8gdjf
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Understanding Students’ Engagement with Personalised Feedback Messages

Abstract: Feedback is a major factor of student success within higher education learning. However, recent changes-such as increased class sizes and socioeconomic diversity of the student population-challenged the provision of effective student feedback. Although the use of educational technology for personalised feedback to diverse students has gained traction, the feedback gap still exists: educators wonder which students respond to feedback and which do not. In this study, a set of trackable Call to Action (CTA) links… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 59 publications
1
0
0
Order By: Relevance
“…The visual representation (see Figure 8) demonstrates students who have received feedback in the form of likes and replies, encouraging them to respond and provide personalized and constructive feedback on their peers' responses. These observations are consistent with the research by Iraj et al (2020). They assert that personalized feedback on posts is essential for raising students' levels of involvement in the future.…”
Section: Replies and Likessupporting
confidence: 90%
“…The visual representation (see Figure 8) demonstrates students who have received feedback in the form of likes and replies, encouraging them to respond and provide personalized and constructive feedback on their peers' responses. These observations are consistent with the research by Iraj et al (2020). They assert that personalized feedback on posts is essential for raising students' levels of involvement in the future.…”
Section: Replies and Likessupporting
confidence: 90%
“…Some critics have suggested that the term's broad range of components makes it more difficult to define it precisely and understand what it really means. Researchers are further perplexed by the debate over whether emotional intelligence (EI) is a talent or a characteristic, which leads to a variety of performance assessments and self-respect questionnaires with countless findings that would be at odds with one another (Iraj et al, 2020;Huynh et al, 2018). Others, however, believed that tests for emotional intelligence (EI) might not be valid because EI was closely related to personality and intelligence (Restubog et al, 2020), and they argued that there was not enough evidence to support the validity of the content of such tools because there was a lack of a sound theoretical foundation and ambiguity in the content of EI measures (Can et al, 2021).…”
Section: Criticisms On Emotional Intelligencementioning
confidence: 99%